Soil Physical and Chemical Properties under Shea Tree (Vitellaria paradoxa) at Different Stages of Growth - Ogwok, Gertrude; Kizza-Nkambwe, Sarah; Kasima, Junior Senyonga; Mpewo, Maxmillan; Alele, Peter O. (East African Nature and Science Organization, 2024)
Shea tree (Vitellaria paradoxa), is one of the dominant agro-forestry species in Otuke district of Northern Uganda. Due to its economic importance and, in line with the numerous threats the tree is faced with, there is an urgent need for measures to conserve this species, for example, through incorporating annual food crops in the Shea tree parkland. This, however, requires a better understanding of tree-soil-food crop interactions. A number of studies of this aspect either considered only the mature Shea tree gardens or did not provide a clear distinction between the physiological states of the Shea tree. This was the motivation for this study where we compare variation in soil properties under mature and young Shea tree gardens with sites not having trees in Okwang sub-county, Otuke district. Five soil samples (up to 15 cm deep for top soil and 15-30 cm for sub-soil) were obtained per treatment using a soil auger. Our results show that in the top soil, only percent sand varied among the treatments, while, in the sub-soil, only percentage nitrogen and average phosphorus varied among the treatments. We also found that percentage top soil organic matter and percentage of sub-soil sand had negative strong correlations with maize and soybean yields, while percentage sub-soil clay had a strong positive correlation with maize and soybean yield. We conclude that variations in soil physical and chemical properties under Mature and Young Shea gardens only occur for those properties that have a direct link to tree residues